Stability Evaluation of Different Oblique Lumbar Interbody Fusion Constructs in Normal and Osteoporotic Condition – A Finite Element Based Study - Bereczki, Ferenc; Turbucz, Mate; Kiss, Rita; Eltes, Peter Endre; Lazary, Aron (Frontiers in Bioengineering and Biotechnology, 2021)
Introduction: In developed countries, the age structure of the population is currently undergoing an upward shift, resulting a decrease in general bone quality and surgical durability. Over the past decade, oblique lumbar interbody fusion (OLIF) has been globally accepted as a minimally invasive surgical technique. There are several stabilization options available for OLIF cage fixation such as self-anchored stand-alone (SSA), lateral plate-screw (LPS), and bilateral pedicle screw (BPS) systems. The constructs’ stability are crucial for the immediate and long-term success of the surgery. The aim of this study is to investigate the biomechanical effect of the aforementioned constructs, using finite element analysis with different bone qualities (osteoporotic and normal). Method: A bi-segmental (L2–L4) finite element (FE) model was created, using a CT scan of a 24-year-old healthy male. After the FE model validation, CAD geometries of the implants were inserted into the L3–L4 motion segment during a virtual surgery. For the simulations, a 150 N follower load was applied on the models, then 10 Nm of torque was used in six general directions (flexion, extension, right/left bending, and right/left rotation), with different bone material properties. Results: The smallest segmental (L3–L4) ROM (range of motion) was observed in the BPS system, except for right bending. Osteoporosis increased ROMs in all constructs, especially in the LPS system (right bending increase: 140.26%). Osteoporosis also increased the caudal displacement of the implanted cage in all models (healthy bone: 0.06 ± 0.03 mm, osteoporosis: 0.106 ± 0.07 mm), particularly with right bending, where the displacement doubled in SSA and LPS constructs. The displacement of the screws inside the L4 vertebra increased by 59% on average (59.33 ± 21.53%) due to osteoporosis (100% in LPS, rotation). BPS-L4 screw displacements were the least affected by osteoporosis. Conclusions: The investigated constructs provide different levels of stability to the spine depending on the quality of the bone, which can affect the outcome of the surgery. In our model, the BPS system was found to be the most stable construct in osteoporosis. The presented model, after further development, has the potential to help the surgeon in planning a particular spinal surgery by adjusting the stabilization type to the patient’s bone quality.